Os valores pessoais que orientam o comportamento de consumo de jovens universitários como investidores da bolsa - Pinese, Henrique Penatti (2012)
The financial market, for decades, causes interest in the eyes of researchers from Brazil and the world as a major researches focus in the field of management. But the fact is that for too long the focus of the researches was in the field of finance and very few has been done towards this market in the marketing field or even from the perspective of consumer behavior. In this context we sought to highlight the consumer behavior of young collegian investors towards the stock market at Uberlândia MG. The perspective of means-end chain theory aided by laddering as an interview technique, allows us to understand a little more about the behavior of these consumer groups, faced with this type of investment. This perspective asserts that consumer behavior origins from certain product attributes and by consequences and behavioral attitudes may culminate in personal values of the individual. Such connections translate in the form of a map the behavior of that particular consumer group. It was made about thirty in-depth interviews using the laddering methodology with collegian investors between 20 and 30 years old that operate in the stock market through a broker. Therefore, the study indicates that values such as achievement, security, hedonism, self-direction, stimulation and power can direct the young collegian consumer behavior when they are investing in shares of stock. Values such as personal fulfillment and security points to a stable behavior of the younger university investors, as well as values linked to the stimulation represent the exciting life that the young investor looks for when he acquires this type of product.